Analisis penilaian Kinerja Karyawan Menggunakan metode Behaviorally Anchore Rating Scale BARS dan Management By Objectives MBO Di CV Brilliant - Harahap, Abdul Latif; Perdana, Surya (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
CV. Brilliant is a manufacturing company engaged in the convection industry in the manufacture of various types of clothing, namely shirts, t-shirts, school uniforms and office uniforms. In running its business where there are complaints from production employees on work reports regarding performance appraisals that do not have measurable standards so that performance appraisals tend to be subjective, and there is no target and reciprocity on employee performance achievements so that employees feel uncomfortable and unmotivated at work which results in decreased production in the period from January to June 2019. The purpose of this study is to find out the causes of the decline in employee performance and solutions to increase employee productivity, the researchers analyzed using the Behaviorally Anchor Rating Scale (BARS) and Management By Objectives (MBO) methods using SPSS software. From the results of the analysis obtained several factors in the performance appraisal including Personality worth 5,167, Work Behavior 2,069, Quality of work 1,825, Reliability 1,355 work and Managerial 1,028 as well as the existence of standard goals and reciprocity for employees in performance appraisal to increase productivity. Using both methods can solve performance appraisal problems so that employees can work comfortably and full of motivation.